2006
DOI: 10.1002/jsfa.2587
|View full text |Cite
|
Sign up to set email alerts
|

Cumin seed meal as an alternative to wheat bran in commercial laying hen diets

Abstract: To evaluate the nutritional significance of cumin seed meal (CSM) as a commercial poultry feedstuff on laying hen performance and quality of laid eggs, an experiment was conducted using 144 (48-week-old) laying hens receiving diets containing 0, 25 and 50 g CSM kg −1 with or without polyethylene glycol (PEG 6000) and xylanase enzyme (Grindazym  GP 15000) for 9 weeks. Body weight on the first and last days of the experiment and daily egg production and egg weight and weekly feed intake during the first, fifth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…In the present study, it was found that hen-day egg production, egg weight and FCR were significantly improved by substitution of 100% WB with CSM (Table 2). These results are in agreement with MAnSOORI et al (2006) who observed that the addition of 25 or 50 kg/ton of CSM instead of WB improved egg weight and FCR, while body weight and feed intake were not significantly influenced. The improvement in performance may be due to the nutritional value of CSM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, it was found that hen-day egg production, egg weight and FCR were significantly improved by substitution of 100% WB with CSM (Table 2). These results are in agreement with MAnSOORI et al (2006) who observed that the addition of 25 or 50 kg/ton of CSM instead of WB improved egg weight and FCR, while body weight and feed intake were not significantly influenced. The improvement in performance may be due to the nutritional value of CSM.…”
Section: Discussionsupporting
confidence: 93%
“…Out of the 18 amino acids identified, eight were indispensable, and the first limiting amino acid was tryptophan (BADR and GEORGIEv, 1990). Although there are a vast number of reports on the nutritive value and medicinal effects of cumin seeds and the extracted oil in humans and animals (CHInTHU et al, 1997;GAGAnDEEP et al, 2003), there is no documented work on the use of CSM as an ingredient in poultry rations (MAnSOORI et al, 2006).…”
mentioning
confidence: 99%
“…This was particularly notable in birds provided with DTP, which had the maximum feed intake (29.9 g day −1 ), compared with hens fed AM (12.4 g day −1 ) or RB (16.7 g day −1 ). Birds provided with CSM did not consume this by‐product of cumin seed oil factories, presumably because of its poor palatability and astringent taste due to the presence of tannins, as the total measurable phenolic compound and total tannin contents of CSM were 18.2 g kg −1 and 3.7 g tannic acid equivalents kg −1 respectively 29, 30. Thus this group had a loss of body weight similar to that of FW birds.…”
Section: Discussionmentioning
confidence: 92%
“…This by‐product of tomato canneries, comparable to alfalfa meal in protein and dietary fibre and rich in vitamins and minerals, has been successfully used in broiler and laying hen diets 22–28. Cumin seed meal, high in dietary fibre, has also been successfully used as an alternative to wheat bran at up to 50 g kg −1 in broiler and layer rations 29, 30…”
Section: Introductionmentioning
confidence: 99%
“…Presupposed that poultry receives an isonitrogenous and isoenergetic diet, literature reports about an inclusion rate reach up to 50 g•kg −1 of WB in a laying hens' diet [4].…”
Section: Introductionmentioning
confidence: 99%